(untitled) (Journal of the Bangladesh Agricultural University, 2016)
The present study was done to examine the employment and income generation of small farmers through family poultry. The objectives of the study were to identify socio economic features of family poultry, to examine the impact of family poultry on household improvement, to determine cost, return and profitability of family poultry, to identify the problems faced by family poultry farmer and for its improvement. The data were collected from 90 family poultry farms from Sadarupazila and Trishalupazila of Mymensingh district through face to face interview. The result of the study shows that, the average gross return, gross cost and net return of family poultry farms were Tk. 7314.84, Tk. 3698.90 and Tk. 3615.94 respectively. The Benefit cost ratio was 1.98. Therefore, family poultry farm is highly profitable. The study also determined the impact of family poultry production on livelihood of poultry farmers. The income of 60% poultry farms has increased and for savings, it was 32%. The physical assets (agricultural tools and furniture and equipments) of poultry farms have improved by 57% and 27% respectively. Sanitation, drinking water facility and medicinal facility of poultry farmers were improved by 26%, 18% and 37% respectively. It is also found from the study that the livelihood of 38% poultry farmers was improved through family poultry production. J. Bangladesh Agril. Univ. 13(2): 247-254, December 2015